Web3 and blockchain applications for real world problems - Choo, Jin Cheng (Nanyang Technological University, 2024)
In today's increasingly digital world, managing shared expenses within groups remains a challenge despite the availability of centralized solutions like Tricount and Splid. These applications, while convenient, suffer from limitations such as lack of transparency, restricted user control, and inefficient settlement processes, especially for cross-border transactions. With the rapid growth of decentralized finance, there is a growing opportunity to leverage blockchain technology to address these shortcomings.